A new chronology based on OSL and radiocarbon dating for the archaeological settlements of Vadnagar (western India) along with magnetic and isotopic imprints of cultural sediments. (August 2021) - Agnihotri, Rajesh; Patel, Nikhil; Srivastava, Pradeep; Ambekar, Abhijit; Arif, M.; Kumar, Anil; Phartiyal, Binita; Kumar, Alok
Highlights: New chronology based on OSL and Radiocarbon dating for the Vadnagar settlement of western India. Sediment magnetic parameters indicate anthropogenic heating/pedogensis of soils. Carbon isotopes indicate aridity in soils throughout despite recovered agricultural grains of rice, beans and pulses. Abstract: Vadnagar town of western India (North Gujarat) possess continuous human habitation record since 2500 years. Owing to its rich cultural heritage, the town had been visited by Chinese pilgrims including Hiuen Tsang in 640 CE. Recent archaeological excavations at Vadnagar revealed continuous sequence of seven successive cultures from the Early historic (6th century BCE to 4th century BCE) period till present. From 2017 to 18 excavation seasons, 18–20 m accumulation of cultural deposits were found at Ambaghat and Darbargarh localities. To complement and fortify the cultural chronology of these ancient cultural deposits, both conventional radiocarbon (C-14) and optically stimulated dating (OSL) methods were employed. Three C-14 and five OSL dates matched perfectly with the cultural ages of deposits and the entire cultural sequence spanned between 2nd century BCE to 6th century CE. Geochemical proxies (δ 13 C, δ 15 N, C/N ratios) of excavated soil-sediments were measured to infer hydro-environmental conditions while soil magnetic parameters (χlf, χhf and χfd%) were measured to assess anthropogenic heating history. Average δ 13 CTOC values of both trenches (−20.7 ± 3.5‰, −19.5 ± 3.5‰) indicated drier status of soil-sediments. Soil magnetic susceptibilities at lower and higher frequency ranges (χlf and χhf) varied in overlapping ranges i.e. 88.5 ± 43.1 and 121.4 ± 72.1 (10 −8 m 3 kg −1 ) respectively, indicating the presence of super paramagnetic grains in the soil attributable to firing activities of soil-sediment. Average χfd% values (8.3 ± 1.1, 7.7 ± 2.0) indicate excavated soils undergone pedogenic processes.